2020
DOI: 10.1037/pas0000820
|View full text |Cite
|
Sign up to set email alerts
|

Development and initial validation of the Eating Pathology Symptoms Inventory–Clinician-Rated Version (EPSI-CRV).

Abstract: Proper assessment and diagnosis of eating disorders (EDs) are critical to determine to whom prevention and treatment efforts should be targeted, the extent to which treatment is working, and when an individual has recovered. Although existing ED diagnostic interviews have numerous strengths, they also have certain limitations, including poor internal consistency, low discriminant validity, and poor factorstructure replicability. The purpose of the current study was to address problems of past ED diagnostic int… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
17
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6

Relationship

5
1

Authors

Journals

citations
Cited by 17 publications
(17 citation statements)
references
References 39 publications
0
17
0
Order By: Relevance
“…The Interview for Mood and Anxiety Symptoms targets dimensions similar to the IDAS-II, but with an interview format to capture the strengths of clinician-based assessment 80,471,490 . These instruments can be supplemented with the self-rated 90 and clinician-rated 491 versions of the Eating Pathology Symptoms Inventory, which provide comprehensive assessment of eating disorder symptoms. Widely used measures of sexual functioning are problematic 492 , indicating a need for better assessment.…”
Section: Measurementmentioning
confidence: 99%
“…The Interview for Mood and Anxiety Symptoms targets dimensions similar to the IDAS-II, but with an interview format to capture the strengths of clinician-based assessment 80,471,490 . These instruments can be supplemented with the self-rated 90 and clinician-rated 491 versions of the Eating Pathology Symptoms Inventory, which provide comprehensive assessment of eating disorder symptoms. Widely used measures of sexual functioning are problematic 492 , indicating a need for better assessment.…”
Section: Measurementmentioning
confidence: 99%
“…Participants in the parent study were recruited from two midwestern universities and surrounding communities by email, flyers, and community advertisements between 2012 and 2018. Inclusion criteria for the current study were (1) diagnosis of sub‐threshold or full‐threshold BN, and (2) endorsement of both binge‐eating and restricting episodes as measured in the Eating Pathology Symptoms Inventory‐Clinician Rated Version (EPSI‐CRV; Forbush et al, 2020). Sub‐ and full‐threshold diagnoses were included because research has shown that they do not differ in demographic features, comorbid psychopathology, or clinical impairment (Chapa, Bohrer, & Forbush, 2018; Fairweather‐Schmidt & Wade, 2014; Johnson, Forbush, Swanson, & Christensen, 2021; Wade & O'Shea, 2015).…”
Section: Methodsmentioning
confidence: 99%
“…The EPSI-CRV (Forbush et al, 2020) is a semi-structured interview based on the Eating Pathology Symptoms Inventory (EPSI) self-report measure, which assesses eight dimensions of eating pathology (Forbush et al, 2013). The EPSI-CRV assesses ED psychopathology over the past 3 months via the following modules: body dissatisfaction, objective binge eating, cognitive restraint, excessive exercise, restricting, purging, muscle building, and negative attitudes towards obesity.…”
Section: The Eating Pathology Symptoms Inventory-clinician Rated Vers...mentioning
confidence: 99%
See 1 more Smart Citation
“…Participants completed the Eating Pathology Symptoms Inventory‐Clinician Rated Version (EPSI‐CRV), a semi‐structured interview that assesses ED psychopathology and behaviors over the previous 3 months (EPSI‐CRV; Forbush et al, 2020). The EPSI‐CRV collects information necessary to make current ED diagnoses.…”
Section: Methodsmentioning
confidence: 99%